Risks for child cognitive development in rural contexts - Hermida, Maria Julia (2019)
While poverty all over the world is more typical and extreme in rural contexts, interventions to improve cognition in low socioeconomic status (SES) children are for the most part based on studies conducted in urban populations. This paper investigate how poverty and rural or urban settings affect child cognitive performance. Executive functions and non-verbal intelligence performance, as well as individual and environmental information was obtained from 131 5-year-old children. For the same level of SES, children in rural settings performed consistently worse than children in urban settings. These differences could be accounted mostly by the months of past preschool attendance and the father's completed level of education. These results should inform policies and programs for children living in rural poverty worldwide, and specially in Latin America.